Self-Monitoring as a Mediator Between Peer Pressure and Behavioral Conformity - Deshmukh, Arjun; Sharma, Neha (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the mediating role of self-monitoring in the relationship between peer pressure and behavioral conformity among adolescents and young adults in India. Methods and Materials: This research employed a descriptive correlational design with a sample of 449 participants selected based on Morgan and Krejcie’s sample size determination table. Participants, aged 16 to 25, were recruited from various educational institutions across India. Data were collected using standardized instruments: the Peer Pressure Scale, the Self-Monitoring Scale, and the Behavioral Conformity Scale. Descriptive statistics, Pearson correlation analysis, and Structural Equation Modeling (SEM) were conducted using SPSS version 27 and AMOS version 21 to evaluate the direct, indirect, and total effects among the variables and to assess the model fit. Findings: Descriptive statistics revealed moderate levels of peer pressure (M = 28.73, SD = 6.41), self-monitoring (M = 16.58, SD = 4.83), and behavioral conformity (M = 76.42, SD = 11.09). Pearson correlation results indicated significant positive associations between peer pressure and behavioral conformity (r = .58, p < .001), peer pressure and self-monitoring (r = .42, p < .001), and self-monitoring and behavioral conformity (r = .51, p < .001). SEM analysis confirmed that the model had an acceptable fit (χ²/df = 2.28, GFI = 0.95, CFI = 0.96, RMSEA = 0.052), and demonstrated that self-monitoring partially mediated the relationship between peer pressure and behavioral conformity, with both direct (β = 0.41, p < .001) and indirect (β = 0.15, p < .001) paths being significant. Conclusion: The findings highlight the significant influence of peer pressure on behavioral conformity and suggest that self-monitoring plays an important mediating role in this relationship. These results underscore the need to consider individual self-regulation traits when addressing peer-influenced behaviors in adolescence and early adulthood.